A novel Zika virus mouse model reveals strain specific differences in virus pathogenesis and host inflammatory immune responses - Tripathi, Shashank; Balasubramaniam, Vinod R. M. T.; Brown, Julia A.; Mena, Ignacio; Grant, Alesha; Bardina, Susana V.; Maringer, Kevin; Schwarz, Megan C.; Maestre, Ana M.; Sourisseau, Marion; Albrecht, Randy A.; Krammer, Florian; et al. (PLoS pathogens, 2017)
Zika virus (ZIKV) is a mosquito borne flavivirus, which was a neglected tropical pathogen until it emerged and spread across the Pacific Area and the Americas, causing large human outbreaks associated with fetal abnormalities and neurological disease in adults. The factors that contributed to the emergence, spread and change in pathogenesis of ZIKV are not understood. We previously reported that ZIKV evades cellular antiviral responses by targeting STAT2 for degradation in human cells. In this study, we demonstrate that Stat2-/- mice are highly susceptible to ZIKV infection, recapitulate virus spread to the central nervous system (CNS), gonads and other visceral organs, and display neurological symptoms. Further, we exploit this model to compare ZIKV pathogenesis caused by a panel of ZIKV strains of a range of spatiotemporal history of isolation and representing African and Asian lineages. We observed that African ZIKV strains induce short episodes of severe neurological symptoms followed by lethality. In comparison, Asian strains manifest prolonged signs of neuronal malfunctions, occasionally causing death of the Stat2-/- mice. African ZIKV strains induced higher levels of inflammatory cytokines and markers associated with cellular infiltration in the infected brain in mice, which may explain exacerbated pathogenesis in comparison to those of the Asian lineage. Interestingly, viral RNA levels in different organs did not correlate with the pathogenicity of the different strains. Taken together, we have established a new murine model that supports ZIKV infection and demonstrate its utility in highlighting intrinsic differences in the inflammatory response induced by different ZIKV strains leading to severity of disease. This study paves the way for the future interrogation of strain-specific changes in the ZIKV genome and their contribution to viral pathogenesis.